Insulin and leucokinin pathways coordinate adaptive salt appetite in Drosophila - Sonali Puri; Jiun Sang; Prakash Pandey; Youngseok Lee (Proceedings of the National Academy of Sciences, 2026)
Salt intake must be tightly regulated: Too little compromises physiological function, while too much is harmful. Animals therefore display an adaptive salt appetite, dynamically switching between attraction and avoidance depending on internal sodium status. Although this behavioral flexibility is well documented, the central brain mechanisms that link internal salt need to changes in sensory-driven behavior remain poorly understood. Here, we identify a brain-centered neuroendocrine circuit that enables adaptive regulation of salt appetite in Drosophila melanogaster . Using targeted genetic screens, we show that leucokinin ( Lk ), its receptor ( Lkr ), and the insulin-like peptide Ilp2 are essential for shifting salt preference according to sodium deprivation. Under salt-sated conditions, high salt remains aversive. In contrast, salt-deprivation selectively activates Lk neurons in the anterior leucokinin (ALK) region, which in turn recruit Lkr -expressing insulin-producing cells (IPCs), also referred to as medial neurosecretory cells, to promote salt-seeking behavior. Functional imaging and circuit manipulation demonstrate that silencing either neuronal population abolishes this adaptive switch, whereas pathway activation overrides innate salt aversion through PKA-dependent signaling. Notably, both ALK neurons and IPCs directly detect extracellular sodium independent of synaptic input, identifying them as central sodium sensors that couple internal state to behavioral output. Together, our findings define a neuroendocrine mechanism by which the brain adaptively recalibrates salt appetite to maintain internal homeostasis. This work provides a conceptual framework for state-dependent nutrient seeking and suggests conserved principles relevant to salt balance disorders in mammals.